По щучьему веленью: [сказки] / художник Игорь Приходкин - Приходкин И. (Пять сказок, 2011)
Экземпляры: ф14 (20160915) / Инвентарный номер: 52619 / Цена: 50.00 / Сис.шифр: Д / Авт.знак: П 41 / ГРНТИ: 17 / ББК: 82.3(2Рос=Рус)